The Impact of Cirrhosis and History of Hepatocellular Carcinoma on All-Cause Mortality After Eradication of Hepatitis C Virus in Patients With Chronic Hepatitis C - Hidenori Toyoda (Gastro Hep Advances, 2022)
Backgrounds and Aims: Cirrhosis and hepatocellular carcinoma (HCC) are potentially fatal complications of chronic hepatitis C virus (HCV) infection. We investigated how compensated cirrhosis and a history of curatively treated HCC influenced patient mortality after HCV eradication, that is, sustained virologic response (SVR). Methods: We studied 5458 patients with confirmed SVR who were prospectively followed up for more than 1 year after SVR achieved with direct-acting antivirals. Mortality and the incidence of HCC development after SVR were analyzed based on the presence or absence of compensated cirrhosis or a history of curatively treated HCC before the start of therapy. Results: Mortality and the incidence of post-SVR HCC were significantly higher in patients with compensated cirrhosis and those with a history of curatively treated HCC than in those without these complications. Multivariate analysis showed that a history of HCC was associated with high mortality after SVR. In patients with no history of HCC, cirrhosis was associated with high mortality. Although both liver-related and nonliver-related mortality rates were significantly higher in patients with a history of HCC or cirrhosis, nonliver-related mortality did not differ based on HCC history, and liver-related and nonliver-related mortality were comparable regardless of cirrhosis after propensity score matching with age, gender, alcohol intake, and comorbidities. Conclusion: Mortality after SVR was significantly higher in patients with compensated cirrhosis or a history of HCC. While a history of HCC significantly increased mortality after SVR, even following curative treatment, the impact of pre-SVR compensated cirrhosis on post-SVR mortality was modest.